"You can't always get what you want" : prevalence, magnitude, and predictors of the aspiration-attainment gap after the school-to-work transition - Nießen, Désirée [Verfasser]; Wicht, Alexandra [Verfasser]; Schoon, Ingrid [Verfasser]; Lechner, Clemens M. [Verfasser] (My University, 2022)
"This study examined the prevalence, magnitude, and predictors of the aspiration-attainment gap (AAG) after the school-to-work transition. We operationalized the AAG as the discrepancy between the socioeconomic status (SES) of young people’s realistic occupational aspirations and that of the position they actually attained. As a case in point, we investigated non-college-bound students transitioning into a vocational education and training (VET) position in Germany. Our aims were twofold: first, to establish how many students experience an AAG of what size; second, to identify characteristics that predict whether students experience an AAG. We considered sociostructural characteristics, cognitive ability and school grades, and Big Five personality traits as predictors (i.e., potential determinants) of the AAG. Analyses in a representative sample (N = 2,478) of intermediate secondary school (Realschule) students/graduates from the German National Educational Panel Study (NEPS; Starting Cohort 4) revealed that 45.9% of students experienced an AAG. Two-part regression models showed that the level of aspirations was the strongest predictor of the experience and size of an AAG, followed by school grades. Aspirations also mediated the effects of several other predictors, most importantly parental SES and school grades. Parental SES, female gender, and Emotional Stability had contradictory effects: They indirectly increased the risk of experiencing an AAG by raising aspirations, but at the same time they lowered this risk by directly increasing attainment. Overall, our results suggest that the AAG during the transition from school to VET is a widespread experience among students in Germany that is worthy of further investigation." (Authors' abstract, BIBB-Doku)
Keywords: G 1.3.2.2.1 Erste Schwelle, in Ausbildung; G 1.3.2 Bildungsverhalten und -verläufe; P 2.1 Schulabgänger; 370; Berufseinmündung; Erste Schwelle; Bildungsaspirationen; Berufswunsch; Berufswahl; Einflussfaktor; Sozioökonomischer Status; Kognitive Fähigkeit; Notengebung; Persönlichkeitsmerkmal; Realschüler; Schulabgänger; Empirische Untersuchung; Nationales Bildungspanel; Regressionsanalyse